Evaluasi Kinerja Pegawai Berbasis Human Resource Information System (HRIS) di Dinas Pertanian Kabupaten Barito Kuala Menuju Era Society 5.0 - Linda, Linda; Zakky Zamrudi; Syahrial Shaddiq (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Digital transformation in the era of Society 5.0 encourages government agencies to improve the effectiveness of human resource management through the use of information technology. This study aims to analyze the application of the Human Resource Information System (HRIS) in employee performance evaluation at the Barito Kuala District Agriculture Office and assess its impact on the efficiency and objectivity of the assessment. The research method used a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, presentation, and conclusion drawing. The results showed that HRIS contributed to accelerating the evaluation process, increasing transparency, and providing more accurate data. However, obstacles were still found in the form of limited digital literacy among employees, suboptimal technological infrastructure, and resistance to change. This study concluded that HRIS is a strategic instrument in supporting digital-based human resource management in line with the Society 5.0 vision, thus requiring the strengthening of human resource capacity and infrastructure to support the sustainability of the performance evaluation system.